Help Musicians UK hearing survey: Musicians' hearing and hearing protection. (July 2020) - Greasley, A. E.; Fulford, R. J.; Pickard, M.; Hamilton, N.
Musicians' hearing has received increased attention due to the rising prevalence of hearing loss among general and musical populations. This paper reports results of a national survey exploring professional musicians' awareness of, and perceptions surrounding, their hearing health, and associated help-seeking behavior including attitudes towards hearing protection. Professional musicians ( N = 693) took part, the majority being orchestral or instrumental musicians. Forty percent of the sample had experienced hearing loss or other hearing issues and many attributed hearing problems to their musical careers. Fifty percent of the musicians were worried about noise at work; however, less than a third had taken a hearing test. Reasons for having a test included subsidized tests and experiencing symptoms of hearing loss or tinnitus, while reasons for not having a test included a lack of awareness about options. Data revealed an on-going tension between a concern to protect hearing and the perceived negative outcomes of wearing protection during musical performance, and highlighted the need for more in-depth research into the experiences of musicians in high-risk instrumental groups (e.g., amplified/band musicians, brass, percussion). Providing advice to musicians about the risks of noise-induced hearing loss (NIHL) prior to experiencing symptoms of hearing loss or tinnitus will support improved protection behavior.